PHYTOSOCIOLOGICAL AND EDAPHIC ATTRIBUTES OF MYRISTICA SWAMP FOREST OF SHENDURNEY WILDLIFE SANCTUARY, KOLLAM, KERALA, INDIA - H . BILYAMINU; K. VIDYASAGARAN; S. GOPAKUMAR (The Bioscan, 2021)
Phytosociological and edaphic attributes studies were carried out in Myristica swamp forest of Shendurney Wildlife Sanctuary. In 2700 m 2 study area, 33 trees species ≥ 10 cm gbh were recorded out of which 14 species were endemic to Western Ghats. The study recorded a total of 309 individuals ( ≥ 10 cm gbh) with a total basal area of 2392.59 m 2 . The forest is dominated by Myristica magnifica, Myristica dactyloides, Knema attenuata, Vateria indica, Hopea parviflora, and Gymnacranthera farquhariana. Myristacaceae family was found to be the dominant one with the important value index of (149.01). Diversity indices such as Shannon–Weiner diversity index (H’) (2.67), and Simpson index of diversity (0.99) were worked out. The edaphic study revealed that the soil is slightly acidic with the pH value (5.39 - 5.67) and with moderate organic carbon (1.33% - 0.46%). This study reported a relatively high number of endemic, endangered, critically endengered vulnerable species, emphasized the increased need for conservation of this important ecosystem.